Metalearning as One of the Task of the Machine Learning Problems - Savchenko, Ye.A.; Rybachok, N.A. (Control systems & computers, 2019)
The concepts of metalearning as one of the tasks of machine learning are considered. The basic principles of metalearning g and examples of solving problems of machine and metalearning in various fields of human activity are given. It is planned for a decision support system construction based on an inductive approach for complex processes modeling and forecasting.